1995
DOI: 10.1177/0310057x9502300609
|View full text |Cite
|
Sign up to set email alerts
|

Limited Usefulness of Urinary Dipsticks to Screen Out Catheter-associated Bacteriuria in ICU Patients

Abstract: The use of urinary dipsticks to screen out sterile urine specimens was investigated in catheterized fCU patients. During a three-month period, each urine sample quantitatively cultured was concurrently tested at the bedside with a dipstick. A total of 101 urine samples taken from 43 patients were analysed. Thirty-eight of them showed bacterial or yeast growths (incidence rate, 37%). The negative predictive value of the leukocyte esterase pad and/or the nitrate test pad to screen out sterile urine samples was 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…UTIs in particular have been extensively diagnosed using devices employing lateral flow assays. While earlier studies on urine dipsticks indicated optimistic results [ 99 ], subsequent studies demonstrated their limitations such as their general low sensitivity [ 20 , 100 ], and particular inaccuracies in cases of uncomplicated UTIs [ 101 ] and catheterized patients [ 102 ]. Similar results were found in a study of UTIs among pregnant women in Tanzania, where it was determined that the dipstick alone was not sufficiently reliable for accurate diagnosis [ 103 ].…”
Section: Lateral Flow Assay For Detecting Utismentioning
confidence: 99%
See 1 more Smart Citation
“…UTIs in particular have been extensively diagnosed using devices employing lateral flow assays. While earlier studies on urine dipsticks indicated optimistic results [ 99 ], subsequent studies demonstrated their limitations such as their general low sensitivity [ 20 , 100 ], and particular inaccuracies in cases of uncomplicated UTIs [ 101 ] and catheterized patients [ 102 ]. Similar results were found in a study of UTIs among pregnant women in Tanzania, where it was determined that the dipstick alone was not sufficiently reliable for accurate diagnosis [ 103 ].…”
Section: Lateral Flow Assay For Detecting Utismentioning
confidence: 99%
“…Klebsiella spp., Staphylococcus aureus, staphylococci, Enterococcus spp., and Candida spp. Urine Colorimetric (dipstick) and cell culture [ 102 ] Leukocyte esterase and nitrite Urine Colorimetric (dipstick) [ 101 ] Leukocyte esterase, nitrite, blood trace Urine Colorimetric (dipstick) [ 100 ] E. coli, Enterococcus spp., Klebsiella pneumoniae Acinetobacter spp., Pseudomonas spp., Morganella spp., S. aureus, Streptococci and Enterobacter spp. Urine Colorimetric (dipstick) and cell culture [ 103 E. coli, Staphylococcus saprophyticus (monoclonal antibodies) Urine Colorimetric [ 105 ] Schistosomes (worm circulating anodic antigen (CAA)) Urine 10 pg/mL to 0.03 pg/mL when increasing urine sample input from 10 μL to 7.5 mL [ 104 ] Enterobacter, Klebsiella, Acinetobacter (nitrate) Urine Colorimteric (dipstick) and cell culture [ 108 ] P. mirabilis and other bacilli (proteins, ketones and nitrites) Urine Colorimetric (dipstick) and flow cytometry [ 106 ] …”
Section: Lateral Flow Assay For Detecting Utismentioning
confidence: 99%